Two new records of Begonia for the flora of India from Arunachal Pradesh - Taram, Momang; Borah, Dipankar; Hughes, Mark (Phytotaxa, 2023)
We report two taxa (Begonia medogensis and B. asperifolia) as new records for the flora of India.